Spirometry and mannitol bronchial challenge test among firefighters in Bhuj district: a questionnaire based study - Buch, Kashyap; Chauhan, Vinayak (International Journal of Advances in Medicine, 2017)
Background: Asthma is a common chronic lung disease that inflames and narrows the airways. It causes recurring period of wheezing, chest tightness, shortness of breath and coughing. Methods: A questionnaire, spirometry, direct and indirect airway challenge tests, exhaled nitric oxide, and skin-prick tests were administered prospectively to 100 out of 120 firefighters employed in Bhuj district, Gujarat, India. Asthma was defined as the combination of respiratory symptoms with airway hyper responsiveness. Results: Twenty out of 100 firefighters (12%) had physician-diagnosed asthma, which could be confirmed in 8 firefighters. In contrast, asthma was diagnosed in 28% (28 of 100 firefighters). Wheezing was the most sensitive symptom for the diagnosis of asthma (sensitivity, 88%; specificity, 90%). Conclusions: Asthma was considerably under diagnosed in firefighters. The combination of a structured symptom questionnaire with a bronchial challenge test allows identifying patients with asthma and should routinely be used in the assessment of active firefighters and may be of help when evaluating candidates for this profession.